British film production - FRENCH, H. (PSL Quarterly Review, 2014)
The british film industry is, by virtue of the common language, the most exposed to American competition; but at the same time it can count on a wider domestic market and on easier access to markets in the Commonwealth countries. The present article gives an account of present government policy towards the film industry in Great Britain. Accordingly, the author concentrates attention on four topics: the quota system imposed on exhibitors in favour of British films; the National Film Finance Corporation; the British Film Production Fund; the Entertainments Tax. An assessment is provided for the need for and the present extent of government aid in this field. The author stresses the British film industry’s difficulties in finding adequate outlets for its production on the one hand, and gives small weight to the assistance which the industry obtains from the government on the other. JEL: L80, L88